2008
DOI: 10.1111/j.1365-2966.2008.14002.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between rotating sunspots and flare productivity

Abstract: To understand both the effects of dynamo and the nature of flaring activity, we identified rotating sunspots and then classified them into six types by using the data of Transition Region and Coronal Explorer and Solar and Heliospheric Observatory/Michelson Doppler Imager in Solar Cycle 23. The classification is made by their rotating directions and relative positions (leading or following sunspots), while the corresponding samples are given. The statistics of flares relevant to these sunspots are presented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…We believe that here we have a superposition of a flux rope emerging with negative helicity (as shown by the magnetic tongue/tails structure, and a smaller rotation of the flux rope as a whole). Yan, Qu, and Kong (2008) proposed that the two sunspots with the same rotating direction have higher flare productivity than those with opposite rotating directions, and this scenario makes it easier to store magnetic energy and increase the helicity of the flux tube. Indeed, the present AR was not large flare/CME productive and the first flare (M2.9) was observed on 16 October 2010 associated with a slow CME (speed≈350 km s −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that here we have a superposition of a flux rope emerging with negative helicity (as shown by the magnetic tongue/tails structure, and a smaller rotation of the flux rope as a whole). Yan, Qu, and Kong (2008) proposed that the two sunspots with the same rotating direction have higher flare productivity than those with opposite rotating directions, and this scenario makes it easier to store magnetic energy and increase the helicity of the flux tube. Indeed, the present AR was not large flare/CME productive and the first flare (M2.9) was observed on 16 October 2010 associated with a slow CME (speed≈350 km s −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was found that the twist of the EUV loop structure in the corona is caused by the sunspot rotation (Brown et al, 2001(Brown et al, , 2003Nightingale et al, 2002). The sunspot rotation is often accompanied by flares (Gopasyuk, 1965;Gopasyuk and Lazareva, 1986;Brown et al, 2003;Yan and Qu, 2007;Yan et al, 2008). Observations indicate that twisted loops exist in almost all the flare sites.…”
Section: Introductionmentioning
confidence: 99%
“…The rotation velocity of the sunspots determined from the white light data is 5-6 times less than the azimuthal velocity calculated from the velocity field (Gopasyuk, 1981(Gopasyuk, , 1982Gopasyuk and Kosovichev, 2011). The appearance of the flares strongly correlates with the rotation of the sunspots (Gopasyuk, 1965;Gopasyuk and Lazareva, 1986;Brown et al, 2003;Yan and Qu, 2007;Yan et al, 2008).…”
Section: Introductionmentioning
confidence: 81%